Emotional Quotient Relations, Economic Level, Interests and Learning Styles on Student Achievement Grade Point Average (GPA) at Muhammadiyah University Banten - Albahra, Albahra; Siswosuharjo, Partono (Akademi Keperawatan RSPAD Gatot Soebroto, 2022)
This study aims to determine the relationship between emotional quotient, economic level, interests and learning styles with the level of achievement of the cumulative grade point average (GPA) of students at the University of Muhammadiyah Banten. This type of research uses a cross sectional design. The results of this study were 68% of the respondents who got a 2.00-2.75 GPA, 28% who got a 2.76-3.50 GPA and 4% of the total respondents who got a 3.51-4.00 GPA. . Meanwhile, respondents who had type E personality (Empitizing) were 48%, who had type S personality (Systemising) were 48% and type B (Balance) were 4%. The learning style of students who fall into the Accommodator category is 4%, assimilator is 48% and divergent is 48%. The results of bivariate analysis calculations show that the largest percentage is found in student respondents with a divergent learning style with a GPA of 2.00-2.75 of 80.6% and the lowest percentage is found in students with a GPA of 3.51-4.00 with a learning style that is same, that is, divergent. While student allowances that fall into the category of large allowances are as much as 80%, moderate allowances are as much as 71.8% and small economic allowances are as much as 57.7%. The results of the bivariate analysis showed that the largest percentage was found in respondents with a GPA of 2.00-2.75 with a large allowance of 80% and the lowest percentage was found in respondents with a GPA of 3.51-4.00 with a small allowance of 7.7. Interest in student computer science education as much as 34.7% of students are interested in computer science, as much as 20% are hesitant, and as much as 45.3% are not interested in computer science. The results of bivariate analysis show that the largest percentage is found in respondents who are not interested in computer science with a GPA of 2.00-2.75 at 84.6% and the smallest percentage is in respondents who are interested in computer science with a GPA of 3.51-4 .00 of 5.9%.